A molecular and morphological study of Otocryptis Wagler, 1830 (Squamata: Agamidae) reveals a new genus from the far south of the Western Ghats, Peninsular India - Srikanthan, Achyuthan N.; Adhikari, Omkar Dilip; Ganesh, Sumaithangi Rajagopalan; Deuti, Kaushik; Das, Kalpana; Kulkarni, Vidisha M.; Gowande, Gaurang G.; Shanker, Kartik (Zootaxa, 2021)
In recent years, several studies have revealed significant unknown and cryptic diversity of agamids in peninsular India, particularly in the Western Ghats. Here, we examine the morphology, anatomy and genetics of the sole Indian representative of the otherwise Sri Lankan agamid genus Otocryptis from the Western Ghats. Our analyses reveal significant distinctions in O. beddomii Boulenger, 1885 with respect to the Sri Lankan members, the type species, O. wiegmanni Wagler, 1830, and O. nigristigma Bahir & de Silva, 2005, warranting a new generic placement. To accommodate the divergent and allopatric O. beddomii from the Western Ghats, we erect a new genus Agasthyagama gen. nov. We re-characterise Agasthyagama beddomii (Boulenger, 1885) comb. nov. based on a syntype (ZSI 15733) and recently collected material. In effect, we restrict the genus Otocryptis, represented by two species, O. wiegmanni and O. nigristigma, to Sri Lanka. We also provide a re-appraisal of the genus Otocryptis sensu stricto, based on data from its type species O. wiegmanni. Our finding adds another endemic agamid genus to the Western Ghats, following Salea Gray, 1845, and the recently described Monilesaurus Pal, Vijayakumar, Shanker, Jayarajan & Deepak, 2018, and Microauris Pal, Vijayakumar, Shanker, Jayarajan & Deepak, 2018. In turn, this complements Sri Lankan agamid endemism with Otocryptis, in addition to the accepted endemic radiations of Lyriocephalus Merrem, 1820, Ceratophora Gray, 1835 and Cophotis Peters, 1861. From a systematic perspective, our erection of Agasthyagama gen. nov. likely completes the description of known genus-level diversity in the clade containing Otocryptis Wagler 1830, Sitana Cuvier, 1829 and the recently described Sarada Deepak, Karanth & Giri, 2016.